PENTAHELIX COLLABORATION STRATEGY IN REALIZING ZERO CONFLICT IN BANDUNG CITY TO ACHIEVE NATIONAL SECURITY - Heru Suryanto; Junior Ternama Siahaan; Yusril Ihza Putra Supardi; Rachmat Setiawibawa; Moh Ikhwan Syahtaria; Arifuddin Uksan (Yayasan Amanah Nur Aman, 2025)
National security is no longer confined solely to military threats but has expanded to encompass social, economic, cultural, and political dimensions. Bandung City, as a multicultural and metropolitan area, faces challenges of social conflict arising from urbanization, inequality, and diverse identities. The zero-conflict approach emerges as a preventive strategy emphasizing early detection and the resolution of root social problems to foster stability and harmony. This study aims to explore how the pentahelix collaboration model engaging the government, academia, business sector, community, and media can be implemented to prevent and manage social conflicts in Bandung City and how it contributes to national security. Through literature review and empirical data analysis, this article demonstrates that the pentahelix collaboration effectively creates a responsive and inclusive social ecosystem. Programs such as the Integrated Team for Social Conflict Management (Timdu PKS), Conflict-Alert Neighborhood Units (RW Siaga Konflik), Harmony Villages (Kampung Kerukunan), and the Community Early Detection Forum (FKDM) exemplify multi-stakeholder engagement in early detection, mediation, and public education. The government acts as a regulator, academia provides data and scientific analysis, the business sector supports economic empowerment through CSR initiatives, communities serve as key actors in social mediation, and the media disseminates peace narratives. The findings reveal that the zero-conflict strategy through the pentahelix model not only contributes to local social resilience but also strengthens national stability both structurally and culturally. This model serves as a data-driven and cross-sectoral collaborative policy reference that can be replicated by other regions to achieve sustainable national security.